2001
DOI: 10.1177/073428290101900105
|View full text |Cite
|
Sign up to set email alerts
|

The Social Phobia Scale and the Social Interaction Anxiety Scale: Factor Structure and Reliability in a Spanish-Speaking Population

Abstract: The factor structure of the Social Interaction Anxiety Scale (SIAS) and the Social Phobia Scale (SPS) was evaluated in a Spanish university student sample. The objective of this study was to examine whether these scales are reliable measures in other languages and/or cultures. High levels of internal consistency were found. The results from the factor analyses replicated the structure proposed by the original authors and revealed that both scales are unidimensional and appear to measure different aspects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0
6

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 22 publications
4
41
0
6
Order By: Relevance
“…The SIAS has shown high internal consistency, both among college students (Cronbach's ˛ = .88), and patients with social phobia (Cronbach's ˛ = .93). The Spanish version also demonstrated adequate internal consistency (Cronbach's ˛ = .89) among university students (Olivares, García-López, & Hidalgo, 2001), and in the present study internal consistency was also high (Cronbach's ˛ = .92). Higher scores reflected a greater tendency toward physical comparison.…”
Section: Social Interaction Anxiety Scale (Sias; Mattick and Clarke 19mentioning
confidence: 57%
“…The SIAS has shown high internal consistency, both among college students (Cronbach's ˛ = .88), and patients with social phobia (Cronbach's ˛ = .93). The Spanish version also demonstrated adequate internal consistency (Cronbach's ˛ = .89) among university students (Olivares, García-López, & Hidalgo, 2001), and in the present study internal consistency was also high (Cronbach's ˛ = .92). Higher scores reflected a greater tendency toward physical comparison.…”
Section: Social Interaction Anxiety Scale (Sias; Mattick and Clarke 19mentioning
confidence: 57%
“…Its authors reported high internal consistency (a 5 .93) and a test-retest correlation coefficient above .90. In Spain, Olivares et al [2001] obtained two factors that explain 40.11% of the variance. After carrying out the confirmatory factor analyses, all the items of the SIAS were saturated in a single factor called Interaction Social Anxiety.…”
Section: Instrumentsmentioning
confidence: 98%
“…About one third of the studies investigating the dimensional structure of the SIAS reported that they form a separate factor (see Table 1) while according to other studies only one factor underlies the answers to all 20 SIAS items (Mattick & Clarke, 1998;Olivares et al, 2001). Zubeidat, Salinas, Sierra, and Fernández-Parra (2007) identified even three SIAS factors.…”
Section: Introductionmentioning
confidence: 96%
“…Inconsistent findings, which will be described in more detail in the next section, might be due to different study designs as well as analyses methods and strategies applied in respective studies (see Table 1). For example, in some investigations the dimensionality of the SIAS answers was explored simultaneously with that of the SPS answers (e.g., Habke, Hewitt, Norton, & Asmundson, 1997;Osman, Gutierrez, Barrios, Kopper, & Chiros, 1998;Safren, Turk, & Heimberg, 1998), while for this purpose other studies used only the answers to one of these two scales (e.g., Heinrichs et al, 2002;Mattick & Clarke, 1998;Olivares, Garcia-Lopez, & Hidalgo, 0887-6185/$ -see front matter © 2010 Elsevier Ltd. All rights reserved. doi:10.1016/j.janxdis.2010.03.020 2001; Rodebaugh, Woods, Heimberg, Liebowitz, & Schneier, 2006).…”
Section: Introductionmentioning
confidence: 98%